(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2021)
As the title provocatively suggests, in this article we explore empirically and question on the basis of research outcomes the implications of one of the most distinctive features of Bitcoin as a digital currency: the positively advertised de-centralization of its network and the often derived claim of egalitarianism alleged to the peer-to-peer system. In order to assess degrees and trends of network de-centralization we follow two tracks. First, we analyze a snapshot of BTC transactions taken in October 2020, basing our explorations on a subset of the “crypto_bitcoin” dataset publicly available on Google Cloud Platform and applying some of the more relevant network analysis tools, like degrees and prestige. Then we extend the analysis to the overall Bitcoin system, tracing the structural transformations it has witnessed over time with regard to the hash-rate distribution. Through a longitudinal comparison, we come to show that the number of competitors in the network have decreased over time, reducing the initial outright pluralism of the actors in the system, and gradually melting down into “special nodes”, whose power has grown over time. Such centralization trends, together with the China-centered geographical distribution of the major mining pools, might have had important implications for Bitcoin success as well as they might for its future.